Carbon fiber-reinforced epoxy filament-wound composite laminates exposed to hygrothermal conditioning - Almeida, José Humberto S.; Souza, Samia D. B. [UNESP]; Botelho, Edson C. [UNESP]; Amico, Sandro C. (Springer Nature, 2016)
This study focuses on the evaluation of the effect of hygrothermal conditioning on tensile, compressive, in-plane and interlaminar shear properties, and also on the viscoelastic characteristics of carbon fiber/epoxy laminates. Flat unidirectional laminates were manufactured by dry filament winding and cured under hot compression. The laminates were later exposed to hygrothermal conditioning in a chamber, following the recommendations of ASTM D5229M. All composite coupons were tested before and after conditioning. An analytical Fickian model was used to fit experimental data, showing very good estimates. Shear strength and modulus reduced to about 30 and 38 %, respectively. All specimens presented acceptable failure modes; shear specimens failed at the gage section with delaminations and fiber/matrix debonding, whereas short beam specimens failed via delaminations at the specimen mid-plane. Moisture penetration through the carbon/epoxy surface lead to interfacial debonding and matrix plasticization. Puck’s failure envelope accurately predicted failure under compressive and shear loading.